Point of care ultrasound impact in acute heart failure hospitalization: A retrospective cohort study (2023)
ABSTRACT: Background: Acute decompensated heart failure (ADHF) is one of the most frequent causes of emergency department (ED) visits. Point-of-Care Ultrasound (POCUS) is a reliable, easy-to-use, and available tool for an accurate diagnosis of ADHF. We aimed to analyze the impact of introducing POCUS as an additional tool to clinical standard diagnosis in clinical times of hospitalized heart failure patients. Methods: Retrospective cohort study comparing patients consulting to ED for heart failure acute decompensation previous to the rutinary use of POCUS versus patients who received an ultrasound-guided diagnosis at entrance. Ultrasound evaluation was additional to standard diagnosis (which included natriuretic peptides, images, etc). Cumulative incidence functions were calculated for time to treatment, time to disposition decision, and time to discharge. We used a flexible parametric model for estimate the time ratio (TR) in order to reflect the effect of POCUS. Results: A total of 149 patients were included. The most frequent comorbid condition was hypertension (71.8%) followed by type 2 diabetes (36.2%). B type natriuretic peptide (BNP) was over 500 ng/ml. Most patients had Stevenson B profile (83.9%) at admission. In the cumulative incidence model (Fig. A), the TR (time ratio) for the outcome time to treatment was 1.539 (CI 95% 0.88 to 2.69). The TR for the outcome time to disposition decision was 0.665 (CI 95% 0.48 to 0.99). The TR for the outcome time to discharge (hospital length of stay) was 0.663 (CI 95% 0.49 to 0.90). Conclusion: In our study, the introduction of POCUS to ADHF patients decreases time to disposition decision and total length of hospital stay. Conversely, time to treatment augments. There is need for the evaluation of ultrasound as an intervention in clinical trials to confirm these findings.